The Effectiveness of Education on Handwashing with a Donkey Bridge to Increase Knowledge and Attitudes about Handwashing for Students at the Integrated Islamic Senior High School in Kotagede - Kusbaryanto, Yogyakarta (International Journal of Human and Health Sciences (IJHHS), 2022)
Background: Hand washing is one of the most effective ways to prevent the spread of infectious diseases, both in hospitals and in everyday life. The purpose of this study was to analyze the effectiveness of education about hand washing with a donkey bridge to increase knowledge and attitudes about hand washing in Islamic Terpadu High School students in Kotagede Yogyakarta. Material and Method: This research is a quantitative analytic study with a quasi-experimental research design with a pre-test and post-test group design approach (Polit and Hungler, 1999). The respondents of this study only consisted of the treatment group without the control group. Wilcoxon nonparametric statistical analysis. Data was collected using a questionnaire, ethical approval from the Faculty of Medicine and Health Sciences UMY. Result and Discussion: The results of the statistical test of the difference between pre-test and post-test knowledge about hand washing in the control group obtained a p-value of 0.406 (p> 0.05), there was no difference between the results of the pre-test and post-test on the knowledge of respondents about hand-washing. The results of the statistical test of the difference between the pre test and post test of hand washing attitudes in the treatment group obtained a p value of 0.017 (p < 0.05), this result was significant and there was a significant difference between the results of the pre test and post test on attitudes about hand washing in respondents. Conclusion: Education about hand washing with a donkey bridge is effective in increasing knowledge and attitudes about hand washing in IT SMA students in Kota Gede, Yogyakarta International Journal of Human and Health Sciences Vol. 06 No. 03 July’22 Page: 328-331